Cytotoxic CD4+ T Cells Drive Multiple Sclerosis Progression - Peeters, Liesbet M.; Vanheusden, Marjan; Somers, Veerle; Van Wijmeersch, Bart; Stinissen, Piet; Broux, Bieke; Hellings, Niels (Frontiers in Immunology, 2017)
The disease course of multiple sclerosis (MS) varies greatly between individuals, making prognosis almost impossible. We previously discovered that cytotoxic CD4+ T cells (CD4+ CTL), identified by the loss of CD28, are able to migrate to sites of inflammation, to contribute to tissue damage and to correlate with inflammation, demyelination and disability in an animal model for MS. We hypothesize that CD4+ CTL drive progression of MS and have prognostic value. The percentage of CD4+CD28null T cells was measured in the blood of 176 patients with relapsing-remitting MS (=baseline). Multimodal evoked potentials (EP) combining information on motoric, visual and somatosensoric EP, as well as Kurtzke expanded disability status scale (EDSS) were used as outcome measurements at baseline and after 3 and 5 years. The baseline CD4+CD28null T cell percentage is associated with EP (P=0.003), indicating a link between these cells and disease severity. In addition, the baseline CD4+CD28null T cell percentage has a prognostic value since it is associated with EP after 3 years (P=0.005) and with EP and EDSS after 5 years (P=0.008 and P=0.003). This study provides the first direct link between the presence of CD4+ CTL and MS disease severity, as well as its prognostic value. We elaborate on two research perspectives: 1° investigating strategies to block or reverse pathways in the formation of these cells resulting in new treatments that slow down MS disease progression, 2° including immunophenotyping in prediction modelling studies to aim for personalized medicine.